Polymicrobial community‐acquired pneumonia: An emerging entity. Issue 1 (23rd October 2015) - Cillóniz, Catia; Civljak, Rok; Nicolini, Antonello; Torres, Antoni
Abstract: Polymicrobial aetiology in community‐acquired pneumonia (CAP) is more common than previously recognized. This growing new entity can influence inflammation, host immunity and disease outcomes in CAP patients. However, the true incidence is complicated to determine and probably underestimated due mainly to many cases going undetected, particularly in the outpatient setting, as the diagnostic yield is restricted by the sensitivity of currently available microbiologic tests and the ability to get certain types of clinical specimens. The observed rate of polymicrobial cases may also lead to new antibiotic therapy considerations. In this review, we discuss the pathogenesis, microbial interactions in pneumonia, epidemiology, biomarkers and antibiotic therapy for polymicrobial CAP.